A Code of Professional Ethics for Interior Architects – a Tentative Proposal: Aspirational Ideals and Deontological Obligations - Małek-Orłowska, Monika (Folia Philosophica, 2021)
The article presents two versions of a proposal of a code of professional of ethics for interior architects. The code’s articles reflect both ethical obligations as well as broadly understood aspirational ideals. The two versions of the code emphasize respectively the deontological dimension of professional ethics and the architect’s aspirations. Monika Małek-Orłowska discusses the theoretical assumptions of the proposed code and the methods used in its development. She also addresses the key problems related to its form and content.